Failure mechanisms and structure tailoring of YSZ and new candidates for thermal barrier coatings: A systematic review. (October 2022) - Pakseresht, Amirhossein; Sharifianjazi, Fariborz; Esmaeilkhanian, Amirhossein; Bazli, Leila; Reisi Nafchi, Mehdi; Bazli, Milad; Kirubaharan, Kamalan
Graphical abstract: Highlights: The failure mechanisms and tailoring approaches of thermal barrier coatings were discussed. Doping yttria-stabilized zirconia (YSZ) and nanostructured YSZ are some approaches are investigated recently. New ceramic materials such as lanthanum hexaaluminate and pyrochlore and perovskite oxides show promising high-temperature properties. Abstract: Many factors influence the durability of thermal barrier coatings (TBCs), therefore, in order to tailor these engineering materials for high-temperature applications, it is required to have a comprehensive understanding of the effects of the contributing factors and their interaction for the development of advanced TBCs. This article gives an overview of the failure mechanisms including sintering, TGO growth, thermal shock, CMAS attack, hot corrosion, erosion, and foreign object damage. Also, the approaches that have been investigated to alleviate the adverse effects of the degradation mechanisms were discussed. In addition to chemical and structural modifications of conventional TBCs, new ceramic materials, such as La2 Zr2 O7, La2 Ce2 O7, Gd2 Zr2 O7, SrZrO3, and LaMgAl11 O19, as further candidates for TBC applications were reviewed. These TBC candidate materials have been discussed in terms of their thermal conductivity, thermal expansion coefficients, corrosion resistance characteristics, thermophysical properties, and thermal cycling lifetime.